2022
DOI: 10.1016/j.tranon.2021.101289
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte-derived Exosomal miR-195 Inhibits Osteosarcoma Cell Proliferation and Anti-Apoptotic by Targeting KIF4A in vitro and in vivo

Abstract: Highlights Osteosarcoma (OS) chemoresistance and distant metastasis are directly associated with OS recurrence and dismal patient prognosis, which are serious concerns for the medical community. However, current knowledge on OS pathogenesis and treatment remains limited. We found that kinesin superfamily protein 4A (KIF4A) acts as a potential OS biomarker. KIF4A promoted OS cell proliferation and anti-apoptotic in vitro and enhanced tumor growth in vivo. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…We found that KIF4A can reverse the inhibitory effect of miR‐379‐5p on BC cell migration, invasion, and proliferation. Similar studies have shown that exosomal miR‐195 inhibited osteosarcoma cell proliferation and antiapoptosis in vitro, inhibited tumor growth in vivo, and reduced tolerance to chemotherapeutic drugs by targeting KIF4A 36 . These results suggest that miR‐379‐5p inhibits BC progression by downregulating KIF4A.…”
Section: Discussionsupporting
confidence: 69%
“…We found that KIF4A can reverse the inhibitory effect of miR‐379‐5p on BC cell migration, invasion, and proliferation. Similar studies have shown that exosomal miR‐195 inhibited osteosarcoma cell proliferation and antiapoptosis in vitro, inhibited tumor growth in vivo, and reduced tolerance to chemotherapeutic drugs by targeting KIF4A 36 . These results suggest that miR‐379‐5p inhibits BC progression by downregulating KIF4A.…”
Section: Discussionsupporting
confidence: 69%
“…Early detection and treatment of osteosarcoma patients cannot be overstated [ 16 ]. It has an early onset age, a high malignancy, a high rate of metastasis, and a bad prognosis [ 17 ]. Its proclivity for metastasizing is the most common cause of therapy failure and poor prognosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells at the logarithmic growth phase were seeded in a 6-well plate and grown to 30%–50% confluence. Subsequently, the cells were transfected with overexpression plasmid DNA, short hairpin RNA (shRNA), or empty vectors (pLVX) (the aforementioned plasmids had all been purchased from GenePharma, Shanghai, China) using Lipofectamine 3000 (Invitrogen) according to the manufacturer’s instructions [20] . The gene silencing efficiency of the shRNA was confirmed using quantitative real-time polymerase chain reaction (qRT-PCR).…”
Section: Methodsmentioning
confidence: 99%